2014
DOI: 10.3109/01443615.2014.920796
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a prematurity-based protocol for management of infants born to mothers with Group B Streptococcus colonisation

Abstract: The aim of this study was to validate the efficacy of a protocol for the management of infants born to colonised mothers with Group B Streptococcus (GBS). We studied a cohort of newborns admitted at the A. Gemelli University Hospital between May 2006 and December 2009. A total of 1,108 were newborns of mothers with GBS; 178 were children of mothers with unknown GBS status. Newborns were managed according to the care protocol in use at our division. Infected infants were born to mothers who underwent inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, the proportion of inadequate IAP reported in our study seems lower than that reported by other previous Italian studies [3,32,33]. The 3 documented cases of early neonatal GBS infection provide an incidence equal to 0.71/1,000 live births, a value that is slightly higher, but still in line with the values reported by previous Italian and international studies [2,3,5,[34][35][36][37][38]. In all three of these cases, born in peripheral maternity units, IAP was inadequate.…”
Section: N Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the proportion of inadequate IAP reported in our study seems lower than that reported by other previous Italian studies [3,32,33]. The 3 documented cases of early neonatal GBS infection provide an incidence equal to 0.71/1,000 live births, a value that is slightly higher, but still in line with the values reported by previous Italian and international studies [2,3,5,[34][35][36][37][38]. In all three of these cases, born in peripheral maternity units, IAP was inadequate.…”
Section: N Discussionsupporting
confidence: 82%
“…IAP was carried out in about 87% of the births from a GBS positive mother and this estimate was made possible by having the data from the SIO, taking also into account the under-registration and sometimes inaccurate registration of this data in the HDA database. The proportion of subjects receiving IAP appears to be higher than that reported by previous Italian studies [3,5,[32][33][34]. IAP is not carried out in scheduled caesarean births, due to the very low risk of transmission of GBS to the fetus/newborn and this is recorded in all provincial maternity units [22].…”
Section: N Discussionmentioning
confidence: 90%
“…The total population of women who present at term with unknown GBS status was further stratified for the presence or absence of risk factors. As outlined in Table 1 , the percentage of women who present at term without ROM > 18 hours ranged from 61.8 10 to 91.6% 11 in previous studies. As outlined in Table 2 , the percentage of women who present at term without MIF ranged from 97.8 10 to 99% 16 in previous studies.…”
Section: Methodsmentioning
confidence: 82%
“…As outlined in Table 1 , the percentage of women who present at term without ROM > 18 hours ranged from 61.8 10 to 91.6% 11 in previous studies. As outlined in Table 2 , the percentage of women who present at term without MIF ranged from 97.8 10 to 99% 16 in previous studies. These percentages were used to determine the proportion of the total population of women giving birth in the United States annually who would not have been treated based on the current ACOG guidelines.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation